A rare haematological disorder in a Sudanese child: Evans syndrome, case report and literature review - Bashir, Bashir Abdrhman (Sudan J Paediatr, 2021)
Evans syndrome is a condition in which autoimmune-mediated red blood cells and platelet destruction happens consecutively. It may be associated with a reduction in neutrophil count as a result of immune neutropenia. No sex preference is known and it presents in all ages and any ethnic cohort. Generally, this syndrome tends to be chronic and is characterised by remission and exacerbation. We document a case of the immune-mediated disease associated with Epstein-Barr virus infection in an 8-year-old boy from eastern Sudan who presented with both immune thrombocytopenia purpura and autoimmune haemolytic anaemia. Complete blood count and peripheral blood picture revealed features consistent with immune haemolytic anaemia (rouleaux formation and spherocytes) and thrombocytopenia. Direct anti-human globulin test and indirect anti-human globulin test were positive. Evans syndrome is a potentially life-threatening condition due to the concomitant existence with antiplatelet and anti-erythrocyte antibodies distinguished by a positive antiglobulin test and possibly linked to other autoimmune or lymphoproliferative diseases.